Distributional Impact Analysis: Toolkit and Illustrations of Impacts beyond the Average Treatment Effect - Guadalupe Bedoya; Luca Bittarello; Jonathan Davis; Nikolas Mittag (Institute of Labor Economics (IZA), 2018)
Program evaluations often focus on average treatment effects. However, average treatment effects miss important aspects of policy evaluation, such as the impact on inequality and whether treatment harms some individuals. A growing literature develops methods to evaluate such issues by examining the distributional impacts of programs and policies. This toolkit reviews methods to do so, focusing on their application to randomized control trials. The paper emphasizes two strands of the literature: estimation of impacts on outcome distributions and estimation of the distribution of treatment impacts. The article then discusses extensions to conditional treatment effect heterogeneity, that is, to analyses of how treatment impacts vary with observed characteristics. The paper offers advice on inference, testing, and power calculations, which are important when implementing distributional analyses in practice. Finally, the paper illustrates select methods using data from two randomized evaluations.
Keywords: C18; C21; C54; C93; D39; 330; distribution of treatment effects; impacts on outcome distributions; heterogeneous treatment effects; distributional impact analysis; policy evaluation; random control trials